Heroes. Season 2. - Panettiere, Hayden; Larter, Ali, 1976-; Oka, Masi; Pasdar, Adrian, 1965-; Ramamurthy, Sendhil, 1974-; Ventimiglia, Milo, 1977-; Grunberg, Greg (Universal City, CA : Universal, 2007)
Select people from all over the world are slowly discovering that they have special powers. Now they are learning about each other and must come together to stop one man from taking their powers for himself.
disc 1. Four months later... ; Lizards ; Kindred -- Bonus features: Hereos: Season 2, "A new beginning" ; Deleted scenes ; Audio commentaries with cast & crew -- disc 2. The kindness of strangers ; Fight or flight ; The line -- Bonus features: Takezo Kensel: Sword saint ; The Drucker files ; Deleted scenes ; Audio commentaries with cast & crew -- disc 3. Out of time ; Four months ago... ; Cautionary tales -- Bonus features: Genetics of a scene ; Deleted scenes ; Audio commentaries with cast & crew. disc 4. Truth & consequences ; Powerless -- Bonus features: Season 3 sneak peek ; "Generations" alternate ending ; Inside the alternate ending of "Generations" ; Untold stories ; NBC.com featurettes ; Tim Sale Gallery of screen art -- Audio commentaries with cast & crew.
Originally broadcast on television during the 2007-2008 season.
DVD.
In English with optional English (SDH), French or Spanish subtitles.
Keywords: Superheroes -- Drama; Television serials; Adventure television programs; Fantasy television programs